Proceedings of the 2016 International Conference on Public Management (ICPM 2016) 2016
DOI: 10.2991/icpm-16.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity of Local Leaders to Improve Performance of New Autonomous Region (Dob) in Indonesia

Abstract: This study conducted in Seluma district as County decentralized mandates as beneficiary with the DOB policy formation on the basis of Act No. 3 in 2003, is a wise step in order to achieve the goal of autonomous region. Bases on the study results, the performance of Ministry of Intern Country, Seluma district DOB revealed low. Of all the stakeholders involved, the people most instrumental states that the management conclude up failed or successful an area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…It means that professional Human Resources can achieve the goals set. Several studies that the authors have carried out explain that the capacity of qualified human resources will have implications for organizational performance (Darmi & Suwitri, 2017), in addition, it is essential to have the capability of leaders in organizational governance activities so that organizational governance can run as expected (Darmi, Suwitri, Yuwanto, & Sundarso, 2016;Selo, Ode, La Elwan, & Rizal, 2018).…”
Section: Figure 1 Existing Fort Marlborough Cultural Propertymentioning
confidence: 99%
“…It means that professional Human Resources can achieve the goals set. Several studies that the authors have carried out explain that the capacity of qualified human resources will have implications for organizational performance (Darmi & Suwitri, 2017), in addition, it is essential to have the capability of leaders in organizational governance activities so that organizational governance can run as expected (Darmi, Suwitri, Yuwanto, & Sundarso, 2016;Selo, Ode, La Elwan, & Rizal, 2018).…”
Section: Figure 1 Existing Fort Marlborough Cultural Propertymentioning
confidence: 99%
“…In managing an organization it is important to increase capacity in a programmed and continuous manner [8]. Organizational capacity elements both internally and externally are strived to increase capacity so that organizational goals can be achieved [9]; (Link, 2007) Strengthening institutional capacity, the role of the leadership is very dominant [10] the leadership factor that greatly influences the extent to which institutional capacity can be carried out. Horton explained that one element of institutional capacity can be seen from financial capacity.…”
Section: Economic Concepts In Muhammadiyah Organizationmentioning
confidence: 99%
“…Previous studies have shown that the performance of a new autonomous region (DOB) can be relatively low (Darmi, Suwitri, Yuwanto, & Sundarso, 2016 and contribute to such poor performance (Yuliadi, 2012), Moreover, after separating from its main region, a DOB includes numerous deficiencies from both human and non-human resources (Darmi, Titi & Suwitri, 2017;Tembo, 2004). To fulfill the compulsory and optional affairs of Local Government Law No.…”
Section: Introductionmentioning
confidence: 99%